High levels of viral load monitoring and viral suppression under Treat All in Rwanda – a cross‐sectional study. Issue 6 (14th June 2020) - Ross, Jonathan; Ribakare, Muhayimpundu; Remera, Eric; Murenzi, Gad; Munyaneza, Athanase; Hoover, Donald R; Shi, Qiuhu; Nsanzimana, Sabin; Yotebieng, Marcel; Nash, Denis; Anastos, Kathryn; ,
Abstract: Introduction: Aiming to reach UNAIDS 90‐90‐90 targets, nearly all sub‐Saharan African countries have expanded antiretroviral therapy (ART) to all people living with HIV (PLWH) (Treat All). Few published data exist on viral load testing and viral suppression under Treat All in this region. We assessed proportions of patients with available viral load test results and who were virally suppressed, as well as factors associated with viral suppression, among PLWH in 10 Rwandan health centres after Treat All implementation. Methods: Cross‐sectional study during 2018 of adults (≥15 years) engaged in HIV care at 10 Rwandan health centres. Outcomes were being on ART (available ART initiation date in the study database, with no ART discontinuation prior to 1 January 2018), retained on ART (≥2 post‐ART health centre visits ≥90 days apart during 2018), available viral load test results (viral load measured in 2018 and available in study database) and virally suppressed (most recent 2018 viral load <200 copies/mL). We used modified Poisson regression models accounting for clustering by health centre to determine factors associated with being virally suppressed. Results: Of 12, 238 patients, 7050 (58%) were female and 1028 (8%) were aged 15 to 24 years. Nearly all patients (11, 933; 97%) were on ART, of whom 11, 198 (94%) were retained on ART. Among patients retained on ART, 10, 200 (91%) had available viral load results; of these 9331 (91%) were virally suppressed. Viral suppression was less likely among patients aged 15 to 24 compared to >49 years (adjusted prevalence ratio (aPR): 0.83, 95% CI 0.76 to 0.90 and those with pre‐ART CD4 counts of <200 compared to ≥500 cells/mm 3 (aPR: 0.92, 95% CI 0.90 to 0.93). There was no statistically significant difference in viral suppression among patients who entered after Treat All implementation compared to those who enrolled before 2010 (aPR 0.98, 95% CI 0.94 to 1.03). Conclusions: In this large cohort of Rwandan PLWH receiving HIV care after Treat All implementation, patients in study health centres have surpassed the third UNAIDS 90‐90‐90 target. To ensure all PLWH fully benefit from ART, additional efforts should focus on improving ART adherence among younger persons.